Preoperative red cell distribution width and its relation with in-hospital morbidities including atrial fibrillation after coronary artery bypass - Joshi, Dharmendra; Shrestha, Apurwa; Rahman, Mostafizur; Hoque, Md. Rezwanul (Nepalese Heart Journal, 2024)
Background and Aims: Atrial fibrillation (AF) and other adverse events are significant concerns following coronary artery bypass grafting (CABG). In recent years, Red Cell Distribution Width (RDW) has been identified as a potential biomarker for predicting these adverse outcomes. This study aims to assess early in-hospital adverse events in patients undergoing isolated off-pump CABG (OPCAB) and to analyze the relationship between these events and preoperative RDW levels. Methods: This study prospectively included 150 patients who underwent elective isolated OPCAB procedures. Patients were categorized into an “event group” (those experiencing adverse events) and a “no-event group” (those who did not). Additionally, they were stratified according to preoperative RDW levels into three groups: Group A (RDW ≤14%), Group B (RDW 14-16%), and Group C (RDW ≥16%). A receiver operating characteristic (ROC) curve, followed by both univariate and multivariate regression analyses were utilized to evaluate the predictive value of RDW for in-hospital morbidity. Results: The in-hospital mortality rate was 2.7%, and AF occurred in 20.7% of the patient population. The ROC analysis for early adverse events yielded an Area Under the Curve (AUC) of 0.681 with a p-value <0.001, indicating moderate predictive capability; the sensitivity was 73% and specificity was 64% for RDW ≥14.05%. Multivariate regression analysis demonstrated that RDW independently predicts in-hospital morbidity after OPCAB, with an odds ratio of 0.713 (95% CI 0.566-0.899, p=0.004). Conclusion: Elevated preoperative RDW levels serve as a simple and cost-effective independent predictor of early adverse events following isolated OPCAB.